(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Infectious and inflammatory diseases of the respiratory system caused by Mycoplasma are called respiratory mycoplasmosis (RM). The main pathogen is Mycoplasma pneumoniae. The importance of other mycoplasmas in the course of respiratory infections is still relevant, so the term "respiratory mycoplasmosis" is mainly associated with respiratory infection of M. pneumoniae.